2008
DOI: 10.1177/0269216308092287
|View full text |Cite
|
Sign up to set email alerts
|

Preference for place of care and place of death in palliative care: are these different questions?

Abstract: Place of death is at times suggested as an outcome for palliative care services. This study aimed to describe longitudinal preferences for place of care and place of death over time for patients and their caregivers. Longitudinal paired data of patient/caregiver dyads from a prospective unblinded cluster randomised control trial were used. Patients and caregivers were separately asked by the palliative care nurse their preference at that time for place of care and place of death. Longitudinal changes over time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
232
2
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(246 citation statements)
references
References 21 publications
8
232
2
4
Order By: Relevance
“…Plans may be subject to rapid change as death draws closer. 22,43,51,67,69,70,72,84,85 The National Survey of Bereaved People (VOICES) of bereaved carers reported that, among the 44% of patients who had expressed a preference, 71% had wished to die at home. However, although the majority had died in hospital, most relatives (82%) subsequently felt that the patient had died in the most appropriate place.…”
Section: Preferred Place Of Deathmentioning
confidence: 99%
See 2 more Smart Citations
“…Plans may be subject to rapid change as death draws closer. 22,43,51,67,69,70,72,84,85 The National Survey of Bereaved People (VOICES) of bereaved carers reported that, among the 44% of patients who had expressed a preference, 71% had wished to die at home. However, although the majority had died in hospital, most relatives (82%) subsequently felt that the patient had died in the most appropriate place.…”
Section: Preferred Place Of Deathmentioning
confidence: 99%
“…This was particularly pertinent in relation to the distinction between patients' preferences for place of care and place of death; vague language elides the distinction between these. 69,84 It is evident that there may be a considerable discrepancy between patient and professional recall and understanding of what was said and what was meant in ACP discussions. Misplaced confidence in tacit understanding also inclined professionals to make, and sometimes document, assumptions about patient preferences, which may not correspond with what was actually intended or preferred.…”
Section: Vague Language and Professional Persuasionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Patient preference as to place of death, level of caregiver support and entitlement to private shift nursing were significantly associated with patients dying at home. 3 However, the complex process of decision making about the place of death is often dynamic and contradictory, 4 and involves the patient, the caregivers, and the professionals, 5 as well as environmental factors including hospital or hospice facilities. 2 In Italy, death at home was very frequent in early prospective studies, occurring in as many as 86% of deaths; 6 multivariate analysis showed that a higher degree of family support was associated with home death.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Having a caregiver is still the single most important predictor of home death 11e14 where this is agreed between patient and caregiver. 15,16 Providing end-of-life care can be a positive experience for many people despite the constancy of demands, 17e19 identified emotional concerns, 1 lack of preparation and inability to effectively negotiate the level of involvement, 20e22 poor support and training, significant stressors, 23 limited respite, and a lack of support in transition from the caring role if the person dies. 7,22 While in the role, there are physical and psychological consequences, and in relinquishing the role, a ''hangover'' effect that has measurable adverse health outcomes for caregivers, including mortality.…”
Section: Introductionmentioning
confidence: 99%